2010
DOI: 10.1590/s0037-86822010000600012
|View full text |Cite
|
Sign up to set email alerts
|

Accidents caused by Bothrops and Bothropoides in the State of Paraiba: epidemiological and clinical aspects

Abstract: Introduction: Bothrops and Bothropoides snakes cause 70% of the ophidic accidents in Brazil. The species that cause ophidic accidents in State of Paraíba are Bothropoides erythromelas, Bothrops leucurus and Bothropoides neuwiedi. Methods: This is a prospective and transverse study, following a quantitative approach of accidents involving Bothrops and Bothropoides admitted to the Toxicological Assistance and Information Centers of Campina Grande and João Pessoa (Ceatox-CG and Ceatox-JP), aimed at identifying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
23
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 14 publications
(46 reference statements)
15
23
0
5
Order By: Relevance
“…Albuquerque et al (13) found that in Paraíba state 73.2% of victims were male. Another study on Bothrops snakebites in Paraíba state by Oliveira et al (38) showed a 75.1% predominance of male victims in that region, following the national average.…”
Section: Discussionmentioning
confidence: 90%
“…Albuquerque et al (13) found that in Paraíba state 73.2% of victims were male. Another study on Bothrops snakebites in Paraíba state by Oliveira et al (38) showed a 75.1% predominance of male victims in that region, following the national average.…”
Section: Discussionmentioning
confidence: 90%
“…Several cases were also observed in victims between 30 and 39 years old (13.5%), which is the age range with the largest concentration of individuals engaged in farm labor Later studies also conducted in Paraíba reported that snakebites were most frequent in the age ranges of 10-29 years 18 and 11-20 years 9 . The genus Bothrops was responsible for the great majority of the snakebite cases (74.7%) reported during the studied period.…”
Section: Discussionmentioning
confidence: 97%
“…The information regarding the incidence of snakebites per region, types of venom, deaths, and the consequences of envenomation are essential for evaluating the problem and developing public policies aimed at reducing the number of accidents and improving medical help for victims 6,7 . In spite of a number of previous investigations [8][9][10] , the epidemiology of snakebites in the Northeastern region of Brazil is not yet well understood, most likely due to social and environmental changes that have occurred there in recent decades, the underreporting of snakebite cases, and defi ciencies in collecting epidemiological data. To address this shortcoming, the current study analyzed the clinical and epidemiological profi le of the snakebite cases reported from 2007 to 2012 in the municipalities of the Curimataú region, located in the State of Paraíba in northeastern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos científicos enfatizam que trabalhadores civis e trabalhadores braçais constantemente tornam-se alvos destes acidentes (OLIVEIRA et al, 2010;LIMA et al, 2009). O ambiente propício destes ataques em mulheres e crianças é a própria residência, porém em menor proporção (LIMA et al, 2009 gênero Bothrops e apenas um paciente evoluiu para óbito (LEMOS et al, 2009).…”
Section: Discussionunclassified